Spinal Dural Arteriovenous Fistula, a Rare and Frequently Misdiagnosed Cause of Mielopathy – Case Report and Review of the Literature - Souza, Thiago Magalhães de; Silva, Paulo Gabriel Sacramento da; Paula, Fellipe de; Ghizoni, Enrico; Joaquim, Andrei Fernandes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Spinal dural arteriovenous fistulas (SDAVFs) are rare vascular malformations with unspecific clinical manifestations, which often lead to misdiagnosis and delay in the establishment of effective therapies. Since the neurological prognosis depends on symptom duration and pretreatment neurological status, rapid identification and obliteration of the fistula are key to provide patients with a better quality of life. We herein describe an illustrative case of an elderly patient presenting with progressive myelopathy, with a definitive diagnosis of SDAVF after 18 months of the initial symptoms. We also review the core concepts regarding this condition and discuss strategies to prevent misdiagnosis and worsening of the neurological outcome.
Keywords: arteriovenous fistulas; dural; myelopathy; spinal cord disease